Designing with care: Towards a care-centered model for online learning design. Issue 3 (11th February 2020) - Robinson, Heather; Al-Freih, Maha; Kilgore, Whitney
Abstract : Purpose: The purpose of this study was to explore how care theory and the ethics of care are explained by students in the online environment to clarify the factors that are more relevant in establishing and maintaining caring relations in online learning context. Design/methodology/approach: Utilizing naturalistic inquiry, the researchers interviewed online students and coded transcripts using multiple coding methods within two phases of analysis. Noddings' framework for ethics of care was utilized to identify strategies and practices that enhance each of Noddings' elements in an online course experience. Findings: The findings of this exploratory study provide evidence on how learners perceive being cared for and highlight specific instructor behaviors and course design elements that support the emergence and maintenance of a climate of care in an online learning environment. Indicators of all four elements of Noddings' framework were present in the interviews. Within the themes of each element, strategies and practices to enhance each element in an online course experience are further explained. Research limitations/implications: Establishing a climate of care, whether in traditional or online learning, leads to more inclusive learning experiences that are responsive to the needs of all learners. This study brought to light some of the factors that are more relevant in establishing and maintaining caring relations in online learning context. Originality/value: The findings of this study add to the literature on the role of emotions in an online learning as viewed through the lens of care theory. The findings highlight some strategies and behaviors that promote a climate of care in an online environment from a learner's perspective.